Measuring boldness in decapod crustaceans: an overview of methodological approaches and potential caveats - DeJaegher, Emily; Quijón, Pedro A.; Ramey-Balci, Patricia A. (Frontiers in Ecology and Evolution, 2025)
Behaviours such as boldness (the willingness to take risks) vary within and among species and can influence fitness by indirectly affecting resource competition, mortality risk, reproductive success, and dispersal. As such, many studies have investigated boldness in decapod crustaceans, a group of considerable ecological and economic importance. An initial review of these studies suggested outcome inconsistencies that warrant an examination of the approaches used to measure boldness. Boldness is often quantified by measuring behaviours such as latency to emerge from a shelter, exploration of novel environments, or activity following a threat. Hence, we provide an overview of the growth of research and taxonomic representation and analyse the gaps in the methodological approaches for studies examining boldness in decapods over 20 years (2004 – 2024). An examination of 78 studies indicates steady growth that has been narrow in terms of subject taxonomy and methodologies to measure boldness. The outcomes of these studies are often affected by design choices such as the behaviours measured (some widely used, like shelter use, others more controversial, such as exploratory behaviours), the sex, age, condition, and origin of the subjects, and the experimental or rearing conditions (e.g., acclimation times, density, feeding regime, and temperature). Understanding how methodological choices influence decapod boldness is necessary to improve temporal consistency, ensure reproducibility and reliable comparisons among studies, thereby facilitating meta-analyses. Otherwise, inconsistent reporting of design choices may limit the accuracy and feasibility of such meta-analyses, hindering the synthesis of results.